Implementation of One Stop Service at the Yogyakarta City Licensing Service in Improving the Investment Climate in the City of Yogyakarta in 2020 - Said Hamzali (International Journal of Educational Technology Research, 2023)
One of the innovations built in order to provide the best service is the One Stop Service (PTSP) pattern or what is often called the One Stop Service (OSS). The City of Yogyakarta has a high commitment to increasing economic growth through improving the investment climate. This study aims to find out: 1) the implementation of OSS at the Yogyakarta City Licensing Service in improving the investment climate in 2020, 2) the factors that influence improving the investment climate in 2020. Data collection techniques used were interviews, document studies, and surveys of 50 respondents as OSS service users.